The Concept of Education in Ibn Khaldun's Thought and Its Implications for Today's Islamic Education - Azlan Ihza Agustian; Andi Prastowo; Saripudin (al-Afkar, Journal For Islamic Studies, 2026)
Education plays a strategic role in shaping human beings and civilization. Ibn Khaldun, through his monumental work Al-Muqaddimah, offers an educational concept that is holistic, humanistic, and contextual. This article aims to examine Ibn Khaldun’s educational thought and analyze its implications for contemporary Islamic education. This study employs a qualitative approach using library research, involving the examination of primary and secondary sources relevant to Ibn Khaldun’s educational ideas. The findings indicate that, according to Ibn Khaldun, the purpose of education is not merely oriented toward the acquisition of knowledge, but also toward the formation of moral character, the development of intellectual potential, social preparedness, and the sustainability of civilization. Principles such as gradual learning, the rejection of violence in education, and the emphasis on dialogical relationships between teachers and learners constitute the core characteristics of his educational concept. The implications of Ibn Khaldun’s thought for contemporary Islamic education are reflected in the importance of developing learner-centered curricula, adopting humanistic pedagogical approaches, and strengthening the role of teachers as intellectual and moral guides. Therefore, Ibn Khaldun’s educational thought remains relevant as a conceptual foundation for the renewal and strengthening of Islamic education in the modern era.